Mathematical Model of Power Losses with Regard to Magnetic Fluid Hyperthermia Treatment - Miaskowski, A. (Wydawnictwo Politechniki Łodzkiej, 2018)
"The aim of this study is to propose a mathematical model of single-domain magnetic power losses based on modified linear response and Stoner-Wohlfarth theories. The proposed model can be applied to numerically investigate the heat dissipation from the magnetic nanoparticles dispersed in the tumour during treatment planning. Two scenarios were considered that is the magnetic nanoparticles mobilized and the magnetic nanoparticles immobilized in the tumour. Besides, the eddy currents power losses together with the related temperature distribution were considered in order to analyze the safety issues."

"Celem niniejszej pracy jest prezentacja modelu matematycznego strat magnetycznych dla jednodomenowych nanocząstek magnetycznych. Model opracowano w oparciu o zmodyfikowaną teorię liniowej odpowiedzi, jak i o model Stonera-Wohlfartha. Przedstawiony model może być użyty do analiz numerycznych, mających na celu badanie strat mocy i rozkładu temperatury w tkance rakowej, tj. podczas planowania terapii. W dalszym ciągu, w kontekście układu tkanka rakowa-nanocząstki, rozważono dwa stany nanocząstek magnetycznych – stan statyczny i ruchomy. Ponadto przeprowadzono analizę strat mocy i rozkładu temperatury spowodowanych prądami wirowymi."
Keywords: magnetic fluid hyperthermia; magnetic nanoparticles; mathematical model; power losses; temperature distribution; hipertermia płynu magnetycznego; nanocząstki magnetyczne; model matematyczny; strata mocy; dystrybucja temperatury